The substitution method involves using the expression of one variable extracted from one equation into the other equation.
We have the equation
- 7 x - 14 = 7 y
which can be easily solved for "y" by dividing both sides by "7" :
- x - 2 = y
Then we can substitute the y variable in the second equation:
so we replace y with (- x - 2) in the other equation as shown below:
10 = - 10 x - 5 y
10 = - 10 x - 5 (- x - 2)
use distributive property to remove the parenthesis:
10 = - 10 x + 5 x + 10
10 = - 5 x + 10
subtract 10 from both sides to isolate the term in "x"
0 = - 5 x
divide bothe sides by "-5"
0 = x
Then x = 0, and we can use this value to solve for "y" in the substitution equation:
y = - x - 2
y = - (0) - 2
y = -2
Then the answer is:
x = 0 and y = - 2